2013
DOI: 10.1128/cvi.00222-13
|View full text |Cite
|
Sign up to set email alerts
|

Human Antibody Neutralizes Severe Fever with Thrombocytopenia Syndrome Virus, an Emerging Hemorrhagic Fever Virus

Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV), a newly discovered member of the Bunyaviridae family, is the causative agent of an emerging hemorrhagic fever, SFTS, in China. Currently, there are no vaccines or effective therapies against SFTS. In this study, a combinatorial human antibody library was constructed from the peripheral lymphocytes of 5 patients who had recovered from SFTS. The library was screened against purified virions for the production of single-chain variable-region fragments (Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 32 publications
2
66
0
Order By: Relevance
“…H2A12 was the major binding site of N protein for most human and mouse MAbs. Guo et al [11] confirms that a human monoclonal antibody [6,7], has shown neutralizing activity against SFTSV in vitro and might be used for high risk people in the future. Its neutralizing activity is attributed to blockage of the interactions between the Gn protein and the cellular receptor, indicating that inhibition of virus-cell attachment is its main mechanism.…”
Section: Treatmentmentioning
confidence: 84%
See 2 more Smart Citations
“…H2A12 was the major binding site of N protein for most human and mouse MAbs. Guo et al [11] confirms that a human monoclonal antibody [6,7], has shown neutralizing activity against SFTSV in vitro and might be used for high risk people in the future. Its neutralizing activity is attributed to blockage of the interactions between the Gn protein and the cellular receptor, indicating that inhibition of virus-cell attachment is its main mechanism.…”
Section: Treatmentmentioning
confidence: 84%
“…At present; there is no specific medication to treat this disease. Patients are often treated with Ribavirin, a traditional nonspecific antiviral drug, but its efficacy remains uncertain [10].There is also report says that antibodies play an important role in curing the disease [11]. Neutralizing antibodies can reduce viral load, and prevent SFTSV spreading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of anti-SFTSV human and murine MAbs developed have been nucleocapsid-specific and non-neutralizing. 6,7 The exception was a hMAb recognizing a linear epitope in the ectodomain of Gn found to be capable of neutralizing SFTSV in vitro by blocking virus cell-mediated attachment. 7 The N protein has also been shown to be the immunodominant protein in other phleboviral infections including Rift Valley fever virus (RFTV) and Toscana (TOSV) viruses.…”
mentioning
confidence: 99%
“…6,7 The exception was a hMAb recognizing a linear epitope in the ectodomain of Gn found to be capable of neutralizing SFTSV in vitro by blocking virus cell-mediated attachment. 7 The N protein has also been shown to be the immunodominant protein in other phleboviral infections including Rift Valley fever virus (RFTV) and Toscana (TOSV) viruses. 8,9 It is highly conserved in bunyaviruses and is the most abundantly expressed viral protein in virus-infected cells.…”
mentioning
confidence: 99%